2009
DOI: 10.1007/s11482-009-9064-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Conditions of Quality of Life Among Undergraduate Students: A Cross Sectional Survey

Abstract: Quality of life (QOL) in the context of education is an understudied topic and research related to its’ relation to the sense of coherence (SOC), level of optimism (LOO) and self-efficacy (SE) among students seems to be missing. The rationale for this survey was to fill this gap in knowledge and therefore, the aim of the study is to examine the relationship between students’ QOL and psychological variables such as SOC, LOO and SE, and social ones such as type of faculty, students’ social background and sex. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
1
6
0
3
Order By: Relevance
“…Statistically significant differences between male and female students were found in six out of eight SF-36 scales, where male students had higher scores, all except Physical functioning (PF) and limitations due to physical health (RP). These gender differences are also congruent with the results published in previous studies by Hopman et al (2000), Marshall et al (2008), Posadzki et al (2009), andRakovac et al (2013). Jureša (2000) Our subjects Ware & Gandek (1998) Legend: M = mean; SD = standard deviation; PF = Physical functioning; RP = Role-physical; BP = Bodily pain; GH = General health; VT = Vitality; SF = Social functioning; RE = Role--emotional; MH = Mental health Table 4 shows Pearson product-moment correlations between four personality traits (EPQ), depression symptoms (ZDS) and eight self-perceived health indicators (SF-36).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Statistically significant differences between male and female students were found in six out of eight SF-36 scales, where male students had higher scores, all except Physical functioning (PF) and limitations due to physical health (RP). These gender differences are also congruent with the results published in previous studies by Hopman et al (2000), Marshall et al (2008), Posadzki et al (2009), andRakovac et al (2013). Jureša (2000) Our subjects Ware & Gandek (1998) Legend: M = mean; SD = standard deviation; PF = Physical functioning; RP = Role-physical; BP = Bodily pain; GH = General health; VT = Vitality; SF = Social functioning; RE = Role--emotional; MH = Mental health Table 4 shows Pearson product-moment correlations between four personality traits (EPQ), depression symptoms (ZDS) and eight self-perceived health indicators (SF-36).…”
Section: Resultssupporting
confidence: 93%
“…Page et al (2009) conducted a survey on a large number of Central and East European adolescents and found a significantly higher proportion of boys vs. girls rating their health as very good, and a higher proportion of girls than boys rating themselves as not healthy. Posadzki, Musonda, Debska, and Polczyk (2009) performed a study using SF-36 on a random sample of undergraduate students from 5 different faculties and also found that female students reported lower scores than males on role limitations due to emotional problems (RE), social functioning (SF) and vitality (VT). Rakovac, Pedisic, Pranic, Greblo, and Hodak (2013) recently performed a study on a random sample of Croatian university students using the 12-item Short--Form Health Survey and found that male students scored significantly higher than females on all scales.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Esta se encuentra relacionado con un conjunto de variables tales como las características sociodemográficas (el sexo, la edad, el nivel socioeconómico, el lugar de procedencia, entre otros), las conductas de salud (la actividad física, el consumo alcohol y tabaco, entre otros) y las variables psicológicas (sentido de coherencia, autoeficacia, bienestar, optimismo, entre otros) (Mikolajczyk et al, 2008;Posadzi, Musonda, Debska & Polczyk, 2009;Pekmezovic, Popovic, Tepavcevic, Gazibara & Paunic, 2011;Saravia, 2013;Sabbah, Sabbah, Khamis, Sabbah & Droubi, 2013;Shields & Shoshtari, 2001). La presente investigación se enfocará en las siguientes variables psicológicas: afrontamiento, autoeficacia y adaptación a la vida académica.…”
Section: Determinantes Da Saúde Mental Em Estudantes Universitários Dunclassified
“…There is evidence that single skill deficits also coincide with psychological strain and disability. Recently published research indicates that skill deficits are associated with greater impairment of daily life (e.g., Posadzki, Musonda, Debska, & Polczyk, 2009). Deficits in emotion regulation or social competence were related to greater disability in both the normal population (Extremera & Fernandez-Berrocal, 2002;Segrin & Taylor, 2007) and patients with physical illness (e.g., Grey, Boland, Davidson, Li, & Tamborlane, 2000;Phillips et al, 2009).…”
Section: Journal Of Clinical Psychology April 2015mentioning
confidence: 99%